Impact of Peer Assessment through Google Classroom on Learner’s Writing Skill - John Pahamzah (Journal of English Language Studies, 2022)
This research was to determine the impact of using the "peer-assessment" technique through "google classroom" on student’s writing skills. The sample of this research is the students of class X SMP Indonesian Language. Students of grade ten C for control and grade ten D for the treatment class. The sample were all the students in that class. As the representative of the population, convenience sampling is part of the non-probability sampling used by researchers. Written test was chosen as the research instrument. For the calibration of the items, the researcher used indicators as an assessment rubric by using pre-test and post-test to determine the results of learners' writing skills. The results of this study are the average score (x) of the pre-test learners from treatment was 44 and the average score of the post-test learners as a variable (x) is 71.25. However, the mean score (x) pre-achievement of the learners from the control class was 49.25 and the average score was 79.75. Fulfillment of raters for Google Classroom was insignificant for the learners' composing skills, experimental learners' scores are not better than the control class. Another hypothesis was rejected. The results of the statistical analysis the items showed for the value of sig (2tailed) post-test score was greater than the value (0.92 > 0.05). Therefore, we can conclude that H0 (zero hypothesis) of this study is acceptable.